Гибридная война: сущность и базовые стратегии - Andrievsky, Timur (De Securitate et Defensione. O Bezpieczeństwie i Obronności, 2017)
The main features of arising of a hybrid war were considered, a comparative analysis of the development and progress of “regular”(conventional) and hybrid wars was conducted. Some aspects regarding the formation of a new approach to understanding the phenomenon of hybrid war were elucidated. New classification of armed conflicts is proposed: international armed conflict, armed conflict not of an international character and armed conflict of the hybrid character (hybrid war). That is why it is proposed to consider the hybrid war as a special type of the conflicts of modernity. It is proposed to distinguish the term “hybrid war” and the term “hybrid threats” as elements of aggressor’s preparation to the outbreak of war. Attempt to formulate the complex definition of hybrid war was made for future development of the concept of hybrid wars.